Evaluation of Mechanochemically Prepared CePO4∙H2O Nanoparticles as UV Filter for Photoprotective Formulations - Stanislav Kurajica; Filip Brleković; Sabina Keser; Goran Dražić; Katarina Mužina; Vanesa Mihajlović (Molecules)
Rhabdophane, CePO4∙H2O, nanoparticles were prepared by mechanochemical synthesis with different durations and thoroughly characterized by various characterization techniques. X-ray diffraction analysis showed that the optimal synthesis duration was 15 min, since, in this case, pure rhabdophane is obtained, without traces of contamination by the vessel material. The size of the obtained nanoparticles, as determined from high-resolution transmission electron microscopy images, was around 5 nm. According to UV-Vis diffuse reflectance spectroscopy results, rhabdophane nanoparticles show transparency to visible light and high absorption in the UV region, with a direct bandgap of 3.1 eV. The photocatalytic activity in the Castor oil degradation process and the cytotoxicity for human skin cells were determined and compared to commercial TiO2 nanoparticles, with rhabdophane nanoparticles exhibiting superior properties. Small particle size, purity, absorption in the UV range, transparency to visible light, low photocatalytic activity, and low cytotoxicity indicated the possibility of prepared rhabdophane application as an inorganic UV filter in photoprotective formulations.